Dual veno-arterial extra-corporeal membrane oxygenation support in a patient with refractory hyperdynamic septic shock: a case report. (April 2022) - Porizka, Michal; Rulisek, Jan; Flaksa, Marek; Otahal, Michal; Lips, Michal; Belohlavek, Jan; Balik, Martin
The hypodynamic septic shock appears to be a promising indication to veno-arterial membrane oxygenation (VA-ECMO) support of a patient with insufficient cardiac output. With cardiac recovery most of those patients progress into a hyperdynamic septic shock with cardiac output, which may not match critically low systemic vascular resistance to maintain perfusion pressures. Such refractory distributive shock represents a challenging indication to VA-ECMO. We report a rare case of a 27-year old patient who developed severe refractory hypodynamic septic shock due to the bilateral staphylococcal pneumonia and had to be initially rescued by femoro-femoral VA-ECMO. Despite extensive measures, he remained in intractable hypotension and profound tissue hypoperfusion with imminent multiorgan failure. The commencement of a second jugulo-axillary VA ECMO secured a total blood flow of 14.3 L/min, which restored perfusion pressure and successfully bridged patient over the period of critical haemodynamic instability and ultimately may have facilitated recovery.